Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
How to solve this derivative?
Have to find the first two derivatives of this, but don't remember how to do that with ln
f(x) = (ln(x)) / (1 + e^x)
Thank you!
2 Answers
- 7 years ago
Derivative of lnx is 1/x.
Use the quotient rule.
Or you can change it to (1+e^x)^-1 and use the product rule.
Either way, that is not fun. Good luck.
- Ray SLv 77 years ago
——————————————————————————————————————
Note:
d/dx(lnu) = (1/u)(du/dx)
So,
d/dx(lnx) = (1/x)(dx/dx) = 1/x
———————————————
f(x) = (ln(x)) / (1 + eˣ) ← I'll differentiate using the quotient rule
(1 + eˣ)(1/x) - (ln(x))(0+eˣ)
f '(x) = —————————————–
(1 + eˣ)²
x[(1 + eˣ)(1/x) - (ln(x))(0+eˣ)]
f '(x) = —————————————–— ← Multiplied top and bottom by x to eliminate 1/x
x(1 + eˣ)²
1 + eˣ - xeˣ(ln(x))
f '(x) = —————————— ← ANSWER ... 1st derivative
x(1 + eˣ)²
http://www.wolframalpha.com/input/?i=differentiate...
——————————————————————————————————————
Now, use the quotient rule again to get the 2nd derivative.
Note first that:
d/dx(uvw) = (d/dx(u)·vw) + (d/dx(v)·uw) + (d/dx(w)·uv)
So,
d xeˣ ln x
————— = (eˣ ln x)(dx/dx) + (x ln x)(d/dx(eˣ)) + (xeˣ)(d/dx(ln x))
dx
d/dx(xeˣ ln x) = (eˣ ln x) + (x ln x) eˣ + (xeˣ)(1/x)
d/dx(xeˣ ln x) = eˣ ln x + eˣ x ln x + eˣ
d/dx(xeˣ ln x) = (ln x + x ln x + 1) eˣ
d/dx(xeˣ ln x) = [(1 + x)ln x + 1] eˣ ← Now, we can substitute this as needed
d 1+eˣ–xeˣ ln x
f ''(x) = ———————— ← Now, differentiate using the quotient rule
x(1 + eˣ)²
x(1 + eˣ)²•(0+eˣ-[(1+x)ln x + 1] eˣ) − (1+eˣ–xeˣ ln x)•[x · 2(1+eˣ)eˣ + (1 + eˣ)²·1]
f ''(x) = ———————————————————————————————————
[ x(1 + eˣ)² ]²
-xeˣ(1 + eˣ)²(1+x)ln x − (1+eˣ–xeˣ ln x)(1+eˣ)(2xeˣ+eˣ+1)
f ''(x) = —————————————————————————— ← divide top and bottom by (1+eˣ)
x²(1 + eˣ)⁴
-xeˣ(1 + eˣ)(1+x)ln x − (1+eˣ–xeˣ ln x)(2xeˣ+eˣ+1) ← Expand this and collect like terms
f ''(x) = ———————————————————————
x²(1 + eˣ)³
eˣ(eˣ - 1)x² ln x - (eˣ + 1)(eˣ(2x+1) + 1)
f ''(x) = —————————————————— ← ANSWER ... 2nd derivative
x²(eˣ + 1)³
http://www.wolframalpha.com/input/?i=differentiate...
Hope that is easy enough to follow.
Have a good one!
——————————————————————————————————————